أفعال الكلام في مسرحية "يد واحدة تكفي" للدكتورة فاطمة بخوش - يسرى عوايجية (My University, 2026)
Abstract: This study examines speech acts in the play “One Hand is Enough” through a pragmatic approach based on the Speech Act Theory developed by Austin and Searle. The study aims to reveal how language is employed within theatrical dialogue to construct meaning, express psychological and social conflicts, and advance dramatic events. The research focuses on classifying speech acts in the play into representative, directive, commissive, expressive, and argumentative acts, while highlighting their pragmatic functions in the dramatic discourse. The study also investigates the impact of social, political, textual, and stylistic contexts on shaping the meanings of speech acts, especially within the atmosphere of war and human suffering experienced by the characters. The findings demonstrate that theatrical dialogue in the play goes beyond mere information exchange, becoming a tool of persuasion, influence, and ideological expression, which gives the text a profound pragmatic dimension. The study adopts the descriptive-analytical method to analyze dialogues and relate them to the various contexts within the dramatic text -------------------- ملخص تتناول هذه الدراسة تحليل أفعال الكلام في مسرحية "يد واحدة تكفي" من منظور تداولي، بالاعتماد على نظرية أفعال الكلام عند أوستن وسيرل. وتهدف إلى الكشف عن كيفية توظيف اللغة داخل الحوار المسرحي لبناء المعنى، والتعبير عن الصراعات النفسية والاجتماعية، وتحريك الأحداث الدرامية. وقد ركزت الدراسة على تصنيف الأفعال الكلامية الواردة في المسرحية إلى أفعال توضيحية، وتوجيهية، والتزامية، وعاطفية، وجدلية، مع بيان وظائفها التداولية داخل السياق المسرحي. كما أبرزت الدراسة أثر السياق الاجتماعي والسياسي والنصي في توجيه دلالة الأفعال الكلامية، خاصة في ظل أجواء الحرب والمعاناة الإنسانية التي تعيشها الشخصيات. وأظهرت النتائج أن الحوار المسرحي في المسرحية لا يقتصر على نقل المعلومات، بل يتحول إلى وسيلة للتأثير والإقناع والتعبير عن المواقف الفكرية والإنسانية، مما يمنح النص بعدًا تداوليًا عميقًا. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي لتحليل الحوارات وربطها بالسياقات المختلفة داخل النص المسرحي. ------------------------ Resume Cette etude porte sur l’analyse des actes de langagr dans la piece de theatre une seule main suffit selon une perspective pramatique en s’appuyant sur le theorie des actes de langage d’john austin et de gohn searle. elle vise à mettre en evidence la maniere dont la langue est utilisee dans le dialogue theatral pour construire le sens exprimer les cinfilts psychologiques et sociauux et faire progresser les evenements dramatique. L’etude a adopte une methode descriptive et analytique fondee sur l’analyse des dialogue et leur mise en relation avec ls differents contextes prsents dans le texte theatral
Keywords: Speech Acts .Pragmatics .Theatrical Dialogue .Dramatic Discourse .One Hand is Enough .Pragmatic Context .Language and Action .Dramatic Conflict; أفعال الكلام ،التداولية، الحوار المسرحي، الخطاب المسرحي، مسرحية يد واحدة تكفي، السياق التداولي ،اللغة والفعل ،التحليل التداولي ،الحرب والصورة ـالصراع الدرامي; Actes de la langage pragmatique dialogue theatral discours theatral une suele main suffit contexte pragmatique langue et action analyse pragmatiqu guerre image du conflit dramatique Actes de la langage pragmatique dialogue theatral discours theatral une suele main suffit contexte pragmatique langue et action analyse pragmatiqu guerre image du conflit dramatique